NARRATIVE TEXT WRITING SKILLS IN PGSD STUDENTS - Fransiska Jaiman Madu (Jurnal Cakrawala Pendas, 2024)
Writing a narrative text that includes the main components of the text is not easy. This means that the students' ability in this regard is not entirely good. The evidence is that there are still components that are often ignored and do not appear in the text. The components in question are resolution and coda.  This study aims to assess students' ability to write correct and complete narrative texts. The type of research used is quantitative descriptive research. The sample of this research was 60 students of PGSD Unika Santu Paulus Ruteng. The technique used in collecting data is the test technique. Students were asked to write a narrative text with any theme and pay attention to the right narrative text structure such as orientation, complication, resolution, and coda. The text was analysed using observation technique. Based on the findings, the components of orientation, complication, and resolution in the narrative text get a good range. This is evidenced in the acquisition of student scores which are in the good category and some of them are in the excellent category. The only component of narrative text that needs to be improved is the coda. There are 40 out of 60 students whose scores are in the fair range. Therefore, the coda component needs to be trained. Therefore, the coda component needs to be trained.